ISHLAB CHIQARISH OBYEKTLARINI JOYLASHTIRISHINI KO‘P MEZONLI OPTIMALLASH ASOSIDA BOSHQARUV QARORLARINI QABUL QILISH ALGORITMLARI - Qutlimuratov, Yu.Q.; Risnazarov, A.M. (SCIENCE and SOCIETY, 2024)
The article examines numerical algorithms for solving the problem of location and specialization of agricultural production in a multicriteria form. The methodology for developing a Pareto set for solving multicriteria optimization problems is considered.